Australian Clinical Consensus Guideline: The diagnosis and acute management of childhood stroke. Issue 1 (January 2019) - Medley, Tanya L; Miteff, Christina; Andrews, Ian; Ware, Tyson; Cheung, Michael; Monagle, Paul; Mandelstam, Simone; Wray, Alison; Pridmore, Clair; Troedson, Christopher; Dale, Russell C; Fahey, Michael; et al.
Stroke is among the top 10 causes of death in children and survivors carry resulting disabilities for decades, at substantial cost to themselves and their families. Children are not currently able to access reperfusion therapies, due to limited evidence supporting safety and efficacy and long diagnostic delays. The Australian Clinical Consensus Guideline for the Diagnosis and Acute Management of Childhood Stroke was developed to minimize unwarranted variations in care and document best evidence on the risk factors, etiologies, and conditions mimicking stroke that differ from adults. Clinical questions were formulated to inform systematic database searches from 2007 to 2017, limited to English and pediatric studies. SIGN methodology and the National Health and Medical Research Council system were used to screen and classify the evidence. The Grades of Recommendation, Assessment, Development, and Evaluation system (GRADE) was used to grade evidence as strong or weak. The Guideline provides more than 60 evidence-based recommendations to assist prehospital and acute care clinicians in the rapid identification of childhood stroke, choice of initial investigation, to confirm diagnosis, determine etiology, selection of the most appropriate interventions to salvage brain at risk, and prevent recurrence. Recommendations include advice regarding the management of intracranial pressure and congenital heart disease. Implementation of the Guideline will require reorganization of prehospital and emergency care systems, including the development of regional stroke networks, pediatric Code Stroke, rapid magnetic resonance imaging and accreditation of primary pediatric stroke centers with the capacity to offer reperfusion therapies. The Guideline will allow auditing to benchmark timelines of care, access to acute interventions, and outcomes. It will also facilitate the development of an Australian childhood stroke registry, with data linkage to international registries, to allow for accurate data collection on stroke incidence, treatment, and outcomes.